2020
DOI: 10.11591/ijpeds.v11.i3.pp1603-1609
|View full text |Cite
|
Sign up to set email alerts
|

Decrystallization with high current pulses technique for capacity restoration of industrial nickel-cadmium battery

Abstract: <p>The process of crystallization occurred due to the process of charging and discharging during the usage of the Nickel-Cadmium (Ni-Cd) battery where crystalline formed on the surface of the battery plate. This situation causes the impedance of the Ni-Cd battery increased and contribute to the increment of the battery temperature and battery impedance. High battery temperature will cause the performance of Ni-Cd battery deteriorates. Therefore, this study is investigated on the performance of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…There is a lack of contributions in the specific literature focused on the regeneration of Ni-Cd batteries, although recycling experiences for this technology have been documented, incorporating processes in conjunction with other technologies discussed in this review. The authors only identified [34] as a Ni-Cd-specific publication for battery regeneration processes, which described a method for regenerating Ni-Cd batteries using high-intensity pulses (ranging from 100 A to 300 A) to disrupt the crystalline layer of amorphous nickel hydroxide. Through this approach, they achieved a 41% recovery in battery capacity.…”
Section: Regeneration Systems In Ni-cd Batteriesmentioning
confidence: 99%
“…There is a lack of contributions in the specific literature focused on the regeneration of Ni-Cd batteries, although recycling experiences for this technology have been documented, incorporating processes in conjunction with other technologies discussed in this review. The authors only identified [34] as a Ni-Cd-specific publication for battery regeneration processes, which described a method for regenerating Ni-Cd batteries using high-intensity pulses (ranging from 100 A to 300 A) to disrupt the crystalline layer of amorphous nickel hydroxide. Through this approach, they achieved a 41% recovery in battery capacity.…”
Section: Regeneration Systems In Ni-cd Batteriesmentioning
confidence: 99%